2019
DOI: 10.3233/jad-190010
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Shortening in the Alzheimer’s Disease Neuroimaging Initiative Cohort

Abstract: Background: Although shorter telomeres have been associated with Alzheimer's disease (AD), it is unclear whether longitudinal change in telomere length is associated with AD progression. Objective: To investigate the association of telomere length change with AD diagnosis and progression. Methods: In 653 individuals from the Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort, T/S ratio (telomere versus single copy gene), a proxy of telomere length, was measured for up to five visits per participant (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Likewise, another 2-year follow-up study showed reduced telomere length significantly correlated with dementia in stroke patients (32). Longitudinal investigations did not support the association between shorter telomeres and AD (15, 33). However, the recent meta-analyses with large sample size provided evidence for shorter telomere length and increased risk of AD (11, 12), and most studies have found shorter telomere length in the leukocytes of AD patients (34).…”
Section: Discussionmentioning
confidence: 87%
“…Likewise, another 2-year follow-up study showed reduced telomere length significantly correlated with dementia in stroke patients (32). Longitudinal investigations did not support the association between shorter telomeres and AD (15, 33). However, the recent meta-analyses with large sample size provided evidence for shorter telomere length and increased risk of AD (11, 12), and most studies have found shorter telomere length in the leukocytes of AD patients (34).…”
Section: Discussionmentioning
confidence: 87%
“…A recent longitudinal study on Alzheimer’s disease Neuroimaging Initiative Cohort focused on the TL dynamics concerning late-onset AD risk and progression. Telomere attrition rate did not differ significantly between MCI and AD group, but the later did have significantly shorter TL (Nudelman et al, 2019 ). On the other hand, longer TL at baseline was associated with rapid progression in cerebrospinal fluid biomarkers positive patients from the same cohort (Mahoney et al, 2019 ).…”
Section: Telomere Length In Brainmentioning
confidence: 99%
“…For more details on telomere length acquisition and quality control, see the ADNI telomere methods document on LONI (http://adni. loni.usc.edu/) and Nudelman et al [23].…”
Section: Measurement Of Telomere Lengthmentioning
confidence: 99%